THE EFFECTS OF SENTENCE STRUCTURE MASTERY AND CRITICAL THINKING ON STUDENT’S READING COMPREHENSION - Elyza Martiarini (Deiksis, 2015)
The aim of the research is to obtain empirical data about the effects of sentence structure mastery and critical thinking on student’s reading comprehension. The research was conducted at grade XI from three Private Senior High Schools at South Jakarta. Research method is survey. The sample was taken randomly. There are three kinds of data: data of sentence structure mastery, data of critical thinking, and data of reading compehension. The instrument tests were firstly tried out to determine the validity and reliability. For sentence structuremastery, critical thinking, and reading comprehension’s tests, validity is calculated by Point-Biserial technique and reliability is measured by Split-Half method (Spearman Brown). Research finding shows three point: first, there are significant effects of sentence structure mastery and critical thinking on student’s reading comprehension. Second, there is significant effect of sentence structure mastery on reading comprehension. Third, there is significant effect of critical thinking on student’s reading comprehension.Keywords: Reading Comprehension, Sentence Structure Mastery, Critical Thinking